2020
DOI: 10.1001/jamanetworkopen.2020.12757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Training in Health Disparities in US Internal Medicine Residency Programs

Abstract: IMPORTANCE Health disparities continue to exist despite the call to increase education of health care practitioners. An assessment of health disparities education has not been previously studied in a national cohort. OBJECTIVE To describe and compare the curriculum on health disparities from the perspective of program directors and perceptions of training among internal medicine residents. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional survey study used a survey of US internal medicine program director… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Despite this, few programs have instituted curricula. A study from 2020 among internal medicine residencies found only 39.6% of programs reported having a curriculum on health disparities ( 31 ). Moreover, there is evidence that the task of providing education focused on health disparities and racism falls disproportionately on trainees and faculty from racial and ethnic groups that have been historically underrepresented in medicine, often without resources or support, a phenomenon known as the “minority tax.” ( 32 ) Of the limited number of publications on health disparities training in residency, 94% originate from primary care ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, few programs have instituted curricula. A study from 2020 among internal medicine residencies found only 39.6% of programs reported having a curriculum on health disparities ( 31 ). Moreover, there is evidence that the task of providing education focused on health disparities and racism falls disproportionately on trainees and faculty from racial and ethnic groups that have been historically underrepresented in medicine, often without resources or support, a phenomenon known as the “minority tax.” ( 32 ) Of the limited number of publications on health disparities training in residency, 94% originate from primary care ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…While most internal medicine residents rate the quality of the health equity training they receive as very good or excellent, most program directors do not ( 9 ). This leadership's awareness of the lackadaisical nature of institutional support for health equity training also highlights the magnitude of this gap in education.…”
Section: Discussionmentioning
confidence: 99%
“…Residents who have undergone structural competency report that the training had a positive impact on their clinical practice and relationship with patients ( 8 ). Still, the majority of internal medicine residency curricula do not include health disparities as a topic ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…medicine programs reported a health disparities curricthe majority reported no formal evaluation, thus effectiveness remains unknown. 9 For studies that did have an evaluation component, 10 most focused on lower level outcomes such as learner satisfaction and knowledge change. 14…”
Section: T a G G E D P What's Newmentioning
confidence: 99%